Characteristics of Oxide Layer Formed on the Aluminium (LM6) Alloy and Aluminium (ADC12) Alloy During In-Situ Melting - Saleh, Ts Dr Aslinda (Journal of Advanced Mechanical Engineering Applications, 2021)
In-situ melting also known as in-situ casting is a new alternative in casting process offering a pouring free casting technique which reducing the formation of porosities in aluminium (Al) castings. However, oxidation of the Al during in-situ melting influence its melting phenomenon. This study aims to determine characteristics of oxide layer formed on surface of Al alloy (LM6) and (ADC12) cubes during in-situ melting. Al alloy cubes with approximate dimension (L:1.0cm, W:1.0cm, and H:1.0cm) were placed in a ceramic plate and heated for 30 minutes in a laboratory furnace at the temperatures of 700°C and 750°C for 30 min. The heated samples were prepared for microstructure and elemental analysis using Optical Microscope (OM), Scanning Electron Microscope (SEM) equipped with Energy Dispersive Spectroscopy (EDS), and X-ray Diffraction (XRD). Both Al alloys deformed from a solid uniform cube to a distorted shape after heated at the temperatures of 700°C and 750°C while the colour changed from a shiny and silvery grey to dark grey. Al LM6 alloy cube changed from its shiny and silvery grey (raw sample) to dusty and dark grey mixed with yellow brown at 700°C, while at 750°C it turned to charcoal grey. For Al ADC 12 alloy sample, the colour changed from its shiny and silvery grey to slightly darker grey at 700°C and mixed with yellowish grey at 750°C. The colour changes indicating oxidation of the Al alloys cubes during in-situ melting had occurred, forming superficial layer of aluminium oxide Al2O3. XRD analysis revealed the oxide compounds on the surface of Al LM6 alloy cubes were a complex oxide including Al2O3 hydroxide and spinel. While XRD analysis for Al ADC 12 alloy oxide after heating at the temperature of 750°C contains aluminium oxide hydroxide, suggesting that the aluminium alloy was transformed to the final or stable phase of aluminium oxide (Al2O3).